Pengembangan Aplikasi Penjualan Sepatu Berbasis Web Menggunakan Metode Rapid Application Development - Rismul Trianto Salawali; Ma’ruf Kamil Husain (PT. Global Research Collaboration, 2023)
In today's modern era, where advances in technology and information are developing very rapidly coupled with current advances in technology and information, it has made it easier for customers to carry out transactions and carry out their daily activities. Several shops selling goods, one of which is a shoe store in the Gowa area, are mostly still having trouble getting customers around the store because the location is less crowded by the public. This study aims to create a web-based shoe sales application to try to present shoe sales information to customers quickly and accurately and make it easier for customers to make purchases. The floating method used in developing this web-based shoe sales application system uses the RAD (Rapid Application Development) method. From the results of discussing this web-based shoe sales application, of course, it can be used as a solution to existing problems. With this application it will be very useful in promoting products to a wider range.